Finite element analysis of square tubular T-joints under static loadings - Ahmad Firdaus, Ahmad Asri (2019)
This paper analyses the behaviour of square tubular T-joint by means of numerical studies. Firstly, a static loading is employed to carry out the monotonic static performance on cold-formed square tubular T-joints with different width ratio of brace/chord. The linear analysis of tubular T-joints including the deformation pattern and the development of static loading and displacement will be described. Complementary finite element model for simulating the tubular T-joints under static loading is proposed. Finally, the numerical simulations are carried out to investigate the failure mechanism of T-joints under static loading. The eigenvalue analysis of square tubular T-joints also proposed. Therefore, finite element method will be used to estimate the maximum stress and critical buckling stress. In general, the investigation to reasonably evaluate the static behaviour of square tubular T-joints.